Álgebras derivadamente mansas com três módulos simples - Adriana Xavier Freitas (2016)
Given a finite-dimensional algebra it belongs to one of the following classes: derived tame or derived wild algebras. In this thesis our aim is to determine which finite dimensional K-algebras with three simple modules are derived tame.